Role of Supply Chain and Integration in Logistic Capability Development: Exploring the Importance of Supply Chain and Integration in Textile Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Textile Industry is characterized by a complex production network which spans many businesses and usually crosses International boundaries. It has become an essential commodity in day to day life like food and water. The verities of production in Textile field has spread in all areas right from apparel to Industrial fabrics, protective Textiles, Composite Textiles, Medical textiles, Automotives, Aerospace and in so many other areas. Now- a -days the product range are not within the periphery of one area but reached at nook and corner all over the world.200 respondents were chosen from four textile industries of New Delhi. Four textile industries chosen were Spentex Industries Ltd., Namdev Textiles Industry Pvt. Ltd., Kundkund Textile and Century Textiles Industries Ltd. 50 respondents from each of four industries chosen were participated in the research work and asked about inventory related questions for analysis.